Bahilah di Hulu Sungai Utara: Penebus Dosa Ala Urang Amuntai - Hayati, Siti Muna; Khitam, Husnul (Jurnal Studi Agama dan Masyarakat, 2018)
This study is aimed at examining the Bahilah custom facing a shift in practice and how the views of North Hulu Sungai society towards the Bahilah custom. This study belongs to descriptive qualitative research using observation and interview methods. The study reveals that some modern societies and living in urban areas consider the bahilah custom not based from the Nash (Qur